Single crystal growth and de Haas-van Alphen effect in strong coupling s-wave superconductor SrPt3P. Issue 1 (1st March 2022) - Horie, M; Matsuoka, E; Sugawara, H; Kotegawa, H; Tou, H; Terashima, T; Uji, S
Abstract: We have succeeded in growing a single crystal of SrPt3 P, which was reported as a strong coupling s -wave superconductor with the critical temperature of T c =8.4 K, and have measured the de Haas-van Alphen (dHvA) effect and the electrical resistivity under magnetic fields. Several dHvA frequency branches with the frequencies up to ~ 1 kT with the cyclotron effective masses of mc * = 0.27 – 0.61 m 0 were observed. It was clarified that the superconducting upper critical fields μ0 Hc2 for fields along H // [001] and H // [100] in the tetragonal structure are almost the same in values of μ 0 H c2 ~4.8 T.